Mobile agents in networking and distributed computing - Das, Sajal K. (Hoboken, N.J. Wiley-Interscience, 2012)
"The book focuses on mobile agents, which are computer programs that can autonomously migrate between network sites. This text introduces the concepts and principles of mobile agents, provides an overview of mobile agent technology, and focuses on applications in networking and distributed computing"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Mobile agents (Computer software); Electronic data processing -- Distributed processing; TECHNOLOGY & ENGINEERING / Telecommunications